2016
DOI: 10.1016/j.envpol.2016.05.057
|View full text |Cite
|
Sign up to set email alerts
|

Occurrences, sources and risk assessment of short- and medium-chain chlorinated paraffins in sediments from the middle reaches of the Yellow River, China

Abstract: a b s t r a c tChlorinated paraffins (CPs), one class of hydrophobic and toxic compounds, are easily adsorbed into sediments and then pose potential risks to the ecosystem and human health. However, few researches on short-and medium-chain CPs (SCCPs and MCCPs) in sediments have been performed. In order to comprehensively investigate the spatial distributions, sources, and ecological risks of CPs, sediments collected from the middle reaches of the Yellow River were analyzed by two-dimensional gas chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…The ∑SCCP concentrations in sediments were in the range of not detected (ND)-2020 ng g −1 . The obtained concentrations were lower than those obtained in other studies while similar to the ones obtained in some (Chen et al 2011;Gao et al 2012;Sun et al 2017;Xu et al 2019b;Zeng et al 2017b;Qiao et al 2016), whereas higher in comparison with two studies (Qiao et al 2017;Iozza et al 2008). However, the Mann-Whitney U test indicated that MCCP concentrations in sediments were higher than those of SCCPs (p <0.001), which was attributed to the use pattern of commercial CP formulations in China.…”
Section: Sedimentsupporting
confidence: 81%
“…The ∑SCCP concentrations in sediments were in the range of not detected (ND)-2020 ng g −1 . The obtained concentrations were lower than those obtained in other studies while similar to the ones obtained in some (Chen et al 2011;Gao et al 2012;Sun et al 2017;Xu et al 2019b;Zeng et al 2017b;Qiao et al 2016), whereas higher in comparison with two studies (Qiao et al 2017;Iozza et al 2008). However, the Mann-Whitney U test indicated that MCCP concentrations in sediments were higher than those of SCCPs (p <0.001), which was attributed to the use pattern of commercial CP formulations in China.…”
Section: Sedimentsupporting
confidence: 81%
“…All the extracts were mixed and fractionated by a multilayer silica gel column. The detailed purification process was consistent with previous studies. , The fraction collected was concentrated and mixed with 2.5 ng of ε-HCH in 50 μL of cyclohexane.…”
Section: Methodsmentioning
confidence: 81%
“…Three commerical SCCP mixtures (51.5%, 55.5%, and 63% chlorine contents) and three MCCP mixtures (42%, 52%, and 57% chlorine contents), all at 100 μg/mL in cyclohexane, were obtained from Dr. Ehrenstorfer (Augsburg, Germany). SCCP and MCCP mixtures with other chlorine contents were achieved by mixing CP standard solutions in a certain proportion …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coastal sediments are an important sink for CPs. Data collected from references. ,,,,,,,,,,,, , ,, …”
Section: Distribution Of Cps In the Marine Environmentmentioning
confidence: 99%